THE INFLUENCE OF HEALTH EDUCATION ABOUT GOOD AND CORRECT BREASTFEEDING TECHNIQUES ON THE KNOWLEDGE OF POSTPARTUM MOTHERS IN AISYIYAH PARIAMAN HOSPITAL - ZANAH, MIFTAKHUL; RISHEL, RIKA ASTRIA; YUNTARISA, ATIKA PRADANA (As-Shiha : JOURNAL OF MEDICAL RESEARCH, 2025)
Breast milk (ASI) is an ideal source of nutrition with a balanced composition and adjusted to the needs of infant growth. The implementation of proper and correct breastfeeding is still minimal in postpartum mothers. This study aims to determine the effect of health education on good and correct breastfeeding techniques on the knowledge of postpartum mothers at Aisyiyah Pariaman Hospital. The type of quantitative research with a quasi-experimental design approach to one group pretest and posttest. Samples were taken using purposive sampling technique with a total of 22 respondents. The analysis used was paired sample paired t-test at the α = 5% level. The results of the study showed that 12 (54.5%) postpartum mothers had a low level of knowledge before being given health education on good and correct breastfeeding techniques. The increase in knowledge of postpartum mothers became high, namely 21 people (95.5%) after being given health education on good and correct breastfeeding techniques. The results of the paired t-test showed that p-value = 0.000 <α = 0.05. It can be concluded that there is an influence of providing health education on good and correct breastfeeding techniques on the knowledge of postpartum mothers at Aisyiyah Pariaman Hospital. It is hoped that with this research, the Aisyiyah Pariaman Hospital institution can provide routine counseling to postpartum mothers on how to breastfeed properly.